1994
DOI: 10.1182/blood.v84.9.3040.bloodjournal8493040
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of all-trans retinoic acid on the growth of freshly isolated myeloma cells via interference with interleukin-6 signal transduction [see comments]

Abstract: We showed the dose-dependent growth inhibition by alltrans retinoic acid (ATRA) of myeloma cells freshly isolated from patients. ATRA downregulated the cell surface expression of interleukin-6 receptor (IL- 6R) and/or glycoprotein (gp) 130. The growth-inhibitory activity of ATRA was well correlated with that of anti-gp 130 antibody in every sample. Furthermore, ATRA inhibited the production of IL-6 from both myeloma cells and marrow stromal cells, and recombinant IL-6 (rIL-6) could partially recover the myelom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 0 publications
1
21
0
1
Order By: Relevance
“…Here we report that RA inhibited the proliferation of these two human myeloma cell lines, and provide evidence that this drug modulates the IL-6 autocrine circuit and triggers apoptosis of myeloma cells. RA was shown to down-regulate IL-6R expression on various cells from B lineage, such as Epstein-Barr virus (EBV)transformed lymphoblastoid cells [10], blood B cells from patients with IgM gammopathies [19] and malignant plasma cells [10,11]. In these cases, in vitro treatment with RA leads to a significant, but incomplete down-modulation of IL-6R expression in short-term cultures [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Here we report that RA inhibited the proliferation of these two human myeloma cell lines, and provide evidence that this drug modulates the IL-6 autocrine circuit and triggers apoptosis of myeloma cells. RA was shown to down-regulate IL-6R expression on various cells from B lineage, such as Epstein-Barr virus (EBV)transformed lymphoblastoid cells [10], blood B cells from patients with IgM gammopathies [19] and malignant plasma cells [10,11]. In these cases, in vitro treatment with RA leads to a significant, but incomplete down-modulation of IL-6R expression in short-term cultures [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…RA was shown to down-regulate IL-6R expression on various cells from B lineage, such as Epstein-Barr virus (EBV)transformed lymphoblastoid cells [10], blood B cells from patients with IgM gammopathies [19] and malignant plasma cells [10,11]. In these cases, in vitro treatment with RA leads to a significant, but incomplete down-modulation of IL-6R expression in short-term cultures [10,11]. We found that RA exerted a marked inhibitory effect on proliferation of both U266 and RPMI 8226 cells in early days after addition of the drug which was correlated with loss of viability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that IL-6 signaling plays an important role in the growth of MM, both in vitro and in vivo. (15,17,(36)(37)(38)(39) IL-6 acts as a potent survival and anti-apoptotic factor in MM through activation of multiple signaling cascades. Previous studies have shown that IL-6 induces growth and survival of human myeloma cells by way of the MAPK, (40) JAK/STAT, (31,41,42) and PI3K/Akt kinase pathways, which inhibit apoptosis and the appearance of drug resistance in MM cells.…”
Section: Discussionmentioning
confidence: 99%